Hustle Culture in Generation Z Study of Thematic Hadith - Permatasari, Murnia Andini; Al Ayubi, Sholahuddin; Makhzumi; Alfariz, Ardan; Waesul Kurni (Wardah, 2024)
Analyzing the phenomena known as "hustle culture," which describes a culture of high ambition and intense labor, frequently at the sacrifice of personal wellbeing. Extreme dedication to work, giving up personal time, and internet connectivity that enables people to display their accomplishments are characteristics of hustle culture. This culture has a variety of effects on Generation Z. up the one hand, hustle culture can inspire self-reliance and an entrepreneurial mindset, giving this generation the will to experiment and take up unorthodox professions. On the other hand, the pressure to constantly be productive can lead to mental health problems, stress, and anxiety in addition to interfering with a healthy work-life balance. In contrast to other generations, Generation Z encounters hustling culture in a distinct setting. where their work style and personality are greatly influenced by technology and social media. They are nonetheless impacted by the pressure to succeed, even though they are more conscious of the value of work-life balance. Finding strategies to cope with this strain, foster an atmosphere that promotes wellbeing, and reward success without compromising mental health and interpersonal relationships is crucial for both people and society as a whole.